PARSIFAL gut metagenomic sequencing data (Swedish population) - Bergström, Anna; Pershagen, Göran; Fyhrquist, Nanna; Dühr, Hendrik (Karolinska Institutet, 2025)
To better understand the lifestyle and environmental drivers of the microbiome and resistome we analyzed 74 stool samples from the cross-sectional PARSIFAL study (https://doi.org/10.1111/j.1398-9995.2005.00939.x) using paired-end shotgun metagenomic sequencing. The study population consisted of children aged 5-13 years living in the Uppsala and Järna regions (Sweden) and entailed participants living on farms, children with anthroposophic lifestyles and two reference groups of children living in the same areas but not following these lifestyles. For this study, all 74 fecal samples of the Swedish part of the PARSIFAL study were obtained. Samples were taken by the parents, first stored at –20 °C, and finally stored at –80 °C before DNA extraction, as described by Dicksved et al. (https://doi.org/10.1128/AEM.02223-06). The participant data and samples that were used for the analyses in this study were collected between October 2000 and May 2002. A questionnaire was completed by the parents and has previously been reported in detail by Alfvén et al. (https://doi.org/10.1111/j.1398-9995.2005.00939.x).

The dataset consists of 170 files with a total size of approximately 504 GB.

För att bättre förstå livsstils- och miljöfaktorer som påverkar mikrobiomet och resistomet analyserade vi 74 avföringsprover från den tvärsnittliga PARSIFAL-studien (https://doi.org/10.1111/j.1398-9995.2005.00939.x) med hjälp av parendad shotgun-metagenomsekvensering. Studiepopulationen bestod av barn i åldrarna 5–13 år som bodde i regionerna Uppsala och Järna (Sverige) och inkluderade deltagare som bodde på gårdar, barn med antroposofiska livsstilar samt två referensgrupper av barn som bodde i samma områden men inte följde dessa livsstilar. För denna studie erhölls alla 74 avföringsprover från den svenska delen av PARSIFAL-studien. Prover togs av föräldrarna, först förvarade vid –20 °C och slutligen vid –80 °C före DNA-extraktion, enligt beskrivningen av Dicksved et al. (https://doi.org/10.1128/AEM.02223-06). Deltagardata och prover som användes i analyserna i denna studie samlades in mellan oktober 2000 och maj 2002. Ett frågeformulär fylldes i av föräldrarna och har tidigare rapporterats i detalj av Alfvén et al. (https://doi.org/10.1111/j.1398-9995.2005.00939.x).

Datasetet består av 170 filer med en total storlek på ca 504 GB.
PARSIFAL gut metagenomic sequencing data (Swedish population)
Keywords: Environment and Public Health; Miljö och folkhälsa; Gastrointestinal Microbiome; Tarmflora; HEALTH; HÄLSA; Immunology; Immunologi; Microbiology; Mikrobiologi; Public health; Folkhälsa; Epidemiology; Epidemiologi